Perumusan dan Pengujian Instrumen Alat Ukur Kesabaran Sebagai Bentuk Coping Strategy - Zulmi Ramdani; Tintin Supriyatin; Susi Susanti (Jurnal Psikologi Islam dan Budaya, 2018)
The problem that is difficult to solve can cause stress on the individual. However, individuals have a form of self-control when faced with problem called coping strategy. Coping with stress is a form of an individual's ability to deal with the stress that arises and how a positive respons can change a bad situation to be more comfortable. Islam has already provided  teaching about handling problems, one of them is patience. The purpose of this study is to explore, formulate, describe and analyze patience as a coping strategy for Psychology students. Sequential methods approach is used to answer this problem. The results of the literature study show that patience is more similar to emotion focus coping. At grounded theory, it creates a special model regarding the subject's view of patience which focuses on rational thinking, self acceptance, self control, and effort. The descriptive analysis shows that the patience construct that provided reliable evidence on descriptive SPSS statistics.